Intertextual reelationship between fashion and sculpture (Revista de Ensino em Artes, Moda e Design, 2020)
Intertextual studies, whose object is relational phenomena between different manifestations, find theoretical bases in verbal language. Thus, investigations on vi- suality seek linguistic theories for approximations, which demand analyzes, adjust- ments. From the Bakhtinian concepts “dialogy” and “polyphony”, through Kristeva’s “intertextuality”, as well as “translation” (verbal), approached by numerous authors, Ca- labrese is an exception, as he dealt with translation in the field of visuality. Ramalho e Oliveira and Jardim Filho also exclude each other, presenting intertextual proposals in the visual field. Here, an articulation between sculpture and fashion is analyzed, amal- gamating in images of backs, naked or dressed, the curatorial concept of a show that took place in 2019, in Paris.
Keywords: intertextuality; sculpture and fashion; back side; Emile-Antoine Bourdelle; Palais Galliera